CD11b-Based Pre-Targeted SPECT/CT Imaging Allows for the Detection of Inflammation in Aortic Aneurysm - Zhou X; Zhu K; Zhang Y; Ming Y; Shi D; Tan H; Xiang B; Zhu S; Cheng D; Lai H; Wang C; Liu G (Dove Medical Press, 2022)
Xiaonan Zhou,1,2,* Kai Zhu,1,2,* Yiqiu Zhang,3- 5,* Yang Ming,1,2 Dai Shi,3- 5 Hui Tan,3- 5 Bitao Xiang,1,2 Shichao Zhu,1,2 Dengfeng Cheng,3- 5 Hao Lai,1,2 Chunsheng Wang,1,2 Guobing Liu3- 5 1Department of Cardiac Surgery, Zhongshan Hospital, Fudan University, Shanghai, 200032, People's Republic of China; 2Shanghai Institute of Cardiovascular Diseases, Shanghai, 200032, People's Republic of China; 3Department of Nuclear Medicine, Zhongshan Hospital, Fudan University, Shanghai, 200032, People's Republic of China; 4Institute of Nuclear Medicine, Fudan University, Shanghai, 200032, People's Republic of China; 5Shanghai Institute of Medical Imaging, Shanghai, 200032, People's Republic of China*These authors contributed equally to this workCorrespondence: Guobing Liu, Department of Nuclear Medicine, Zhongshan Hospital, Fudan University, No. 180 in Fenglin Road, Shanghai, 200032, People's Republic of China, Tel +8618317086732, Fax +86-21-62489191, Email liu.guobing@zs-hospital.sh.cn Chunsheng Wang, Department of Cardiac Surgery, Zhongshan Hospital, Fudan University, No. 180 in Fenglin Road, Shanghai, 200032, People's Republic of China, Email wangchunsheng@fudan.edu.cnPurpose: To investigate the feasibility of a pre-targeted imaging strategy based on the cycloaddition between 1,2,4,5-terazine (Tz) and trans-cyclooctene (TCO) for evaluating CD11b expression in inflammatory aortic aneurysm (AA) using single photon emission computed tomography/computed tomography (SPECT/CT).Methods: C57BL/6J mice were fed β-aminopropionitrile (1 g/kg/day) for 4 weeks to establish AA models. Anti-CD11b-TCO was synthesized and 99mTc-HYNIC-PEG11-Tz was designed for pre-targeted SPECT/CT. The affinity and specificity of the probe for the inflammatory cell line Raw-264.7 were investigated. Then, anti-CD11b-TCO pre-targeted and 99mTc-HYNIC-PEG11-Tz based SPECT/CT were performed to detect in vivo inflammation in AA. Finally, ex vivo aortic breast-specific gamma imaging (BSGI), Western blot assays, and immunohistochemical CD11b staining were performed to confirm the in vivo findings of SPECT/CT.Results: In the AA models, 65.22% (15/23) had aortic lesions, including 43.48% (10/23) AA lesions. The anti-CD11b-TCO presented with a high TCO coupling ratio (7.43), and the 99mTc-HYNIC-PEG11-Tz showed high radio-purity (> 95%), good in vitro stability and a rapid clearance rate. Additionally, anti-CD11b-TCO and 99mTc-HYNIC-PEG11-Tz presented high click rate (∼ 89%). The in vitro clicked compound, 99mTc-HYNIC-PEG11-Tz/TCO-anti-CD11b, showed high affinity and specificity for Raw-264.7 cells. 99mTc-HYNIC-PEG11-Tz/TCO-anti-CD11b pre-targeting SPECT/CT successfully demonstrated inflammatory AA with a high AA-to-background ratio in AA mice, compared to AA mice that were injected with 99mTc-HYNIC-Tz/TCO-IgG (8.13 versus 3.71, P < 0.001) and control mice injected with 99mTc-HYNIC-Tz/TCO-anti-CD11b (8.13 versus 3.66, P < 0.001). This result was confirmed by ex vivo BSGI performed immediately after SPECT/CT and immunohistochemical CD11b staining.Conclusion: SPECT/CT imaging using the anti-CD11b-TCO/Tz-PEG11-HYNIC-99mTc based pre-targeting imaging strategy allows for the detection of inflammation in progressive AA.Keywords: aortic aneurysm, inflammation, SPECT/CT, CD11b, macrophage